Strength and microstructural properties of silt soil cured by lime-activated fly ash-GGBS under different curing temperatures - Shunmei Gong; Songbao Feng; Shiquan Wang; Lemei Yu; Yuanyuan Chen; Qiang Xu (Scientific Reports, 2024)
Abstract To reveal the mechanism of the influence of the curing temperature on the strength of lime activated fly ash-GGBS cured silt soil, the curing of dredged silt was carried out by using fly ash and GGBS as the curing agent and lime as the activator. Unconfined compressive strength (UCS) experiments were carried out, and the micro-analysis of the cured silt was carried out by experimental methods including scanning electron microscope (SEM) tests, X-ray diffraction (XRD), etc. to reveal the mechanism of the curing temperature on the dredged silt. According to the test results, the hydration reaction and pozzolanic reaction between lime-fly ash-GGBS and silt soil were promoted with the increase of the curing temperature. when the curing temperature of the sample reached 40 ℃, a large amount of gel products such as hydrated calcium aluminate (C–A–H) and hydrated calcium silicate (C–S–H) were generated, which enhanced the bonding force between soil particles and filled up the inter-particle pore space, thereby improving the UCS of the sample. The results of SEM confirmed that C–A–H and C–S–H were the main substances for the construction of cured silt skeleton. C–S–H and C–A–H were detected by XRD. The results of the study fill the gap in the effect of curing temperature on the direction of lime-activated fly ash-GGBS cured silt soil.